The effect of sex on nutritional status of post-weaned Bligon goats under controlled feeding management - Latifah, Latifah (2019)
Bligon is a crossbred goat that is widely raised in rural areas of Indonesia where goat farming is characterized by low productivity due to the low quality and availability of feed. The aim this study was to test the effect of sex on nutritional status of post-weaned Bligon goats under controlled feeding management. In total 16 post-weaned goats (age 4 months), were fed with the same diets that meet the basic requirements for goat maintenance. They were targeted to reach average daily gain (ADG) of 100 g. The diet contained 14.58% crude protein and 80.78% total digestible nutrient. All goats received 3% to 4% dry matter ratio of the body weight. Water was provided ad libitum. The variables observed were nutrient intake and digestibility, ADG, and feed conversion ratio (FCR). It was found that sex had a significant effect (p<0.05) on crude fiber (CF) intake, ADG and FCR, with mean values of 10.13±1.23 g/kg BW0.75/day, 80.62±25.11 g, and 5.88±1.69 in female goats, respectively, and 11.06±1.64 g/kg BW0.75/day, 132.25±27.71 g, and 3.61±0.62 in male goats, respectively. In can be concluded that sex affects CF intake, ADG and FCR of post-weaned Bligon goats.